2011
DOI: 10.3922/j.psns.2011.2.008
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress, HPA axis, and depression.

Abstract: Considerable evidence from various studies suggests a preeminent role for early adverse experiences in the development of psychopathology, especially depression. The most recent studies reviewed herein suggest that early life stressors are associated with an increased risk for mood disorders in adulthood. This review examines the emerging literature on the relationship between stress, hypothalamic-pituitary-adrenal (HPA) axis function, and depression and the role of early life stress as an important risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Early life stress (ELS) is considered a risk factor for the development of psychopathologies such as anxiety and major depressive illness [1,2] and a contributor to the development of neurodegenerative disorders later in life [3]. Within the brain, ELS promotes a neuroinflammatory state [4], with patients who suffered ELS in childhood showing an increased cytokine response to psychological stressors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Early life stress (ELS) is considered a risk factor for the development of psychopathologies such as anxiety and major depressive illness [1,2] and a contributor to the development of neurodegenerative disorders later in life [3]. Within the brain, ELS promotes a neuroinflammatory state [4], with patients who suffered ELS in childhood showing an increased cytokine response to psychological stressors [5].…”
Section: Introductionmentioning
confidence: 99%
“…These data corroborate results found in previous studies that have indicated that the sequelae in different individuals vary from a few worrying symptoms to clinically relevant levels of maltreatment symptoms, and to the presence of severe psychiatric disorders. [14][15][16][17] Significant differences were also found in Internalizing Problems. For Externalizing Problems, there were no differences between the groups, even though the p value was close to significant.…”
Section: Discussionmentioning
confidence: 59%
“…32 This data can be considered significant if the investigations related to the prevalence of maltreatment in same-age children, recruited from the same region in the city, pointed to neglect. 2,20 Some studies suggest that maltreatment has caused depression and withdrawal, especially because these disorders are commonly associated with individuals' homeostatic imbalance 15 and can harm the brain structuring process, especially in children, during this critical period of their development. 18,19,32 Furthermore, depression and withdrawal, during childhood can lead to isolation, and therefore, generate, in the long-term, new problems with the child's social development as associated with suicide risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in risk related behavior are also time dependent (Henckens et al, 2012) and although we aimed to measure delayed effects of exogenous cortisol, it is possible that some rapid effects remained in some individuals and thus changes in reward based decision making might have been impaired in this instance (Koot et al, 2013). Further to this, HPA axis physiology is determined by previous stressful events associated with hypercortisolism (Herman and Cullinan, 1997; de Carvalho Tofoli et al, 2011) and, therefore, it has been hypothesized that endurance-trained individuals might develop adaptive mechanisms such as decreased sensitivity to cortisol to protect muscle and other glucocorticoid-sensitive tissues against this increased post-exercise cortisol secretion (Duclos et al, 2003). …”
Section: Discussionmentioning
confidence: 99%